2016
DOI: 10.3390/toxins8040118
|View full text |Cite
|
Sign up to set email alerts
|

Application of LC-MS/MS MRM to Determine Staphylococcal Enterotoxins (SEB and SEA) in Milk

Abstract: Staphylococcus aureus is one of the important aetiological agents of food intoxications in Europe and can cause gastro-enteritis through the production of various staphylococcal enterotoxins (SEs) in foods. Due to their stability and ease of production and dissemination, some SEs have also been studied as potential agents for bioterrorism. Therefore, specific and accurate analytical tools are required to detect and quantify SEs. Online solid-phase extraction liquid chromatography electrospray ionization tandem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Different analytical tools have been developed for the detection and quantification of SEs, including immunological and mass spectrometry methods, each of which has its limitations especially on availabilities of specific antibodies, peptides and standards [8,13,30,31]. At this time, commercially available ELISA methods allow routine detection of only five classical SEs, SEA to SEE, in food matrices, with and without identification of the toxin types SEA to SED [6,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Different analytical tools have been developed for the detection and quantification of SEs, including immunological and mass spectrometry methods, each of which has its limitations especially on availabilities of specific antibodies, peptides and standards [8,13,30,31]. At this time, commercially available ELISA methods allow routine detection of only five classical SEs, SEA to SEE, in food matrices, with and without identification of the toxin types SEA to SED [6,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…respectively, in six blinded extracts (four milk samples and two buffer samples). Their results showed that the toxins were successfully detected in milk samples, and the detection limits of SEA and SEB were about 8 and 4 ng/g respectively, levels that are comparable or even lower than those achieved with most of the other identification methods …”
Section: Monitoring Food Safetymentioning
confidence: 89%
“…Several columns have been used to enrich analytes so far, such as the C 18 reverse phase column, ion exchange column and magnetic beads [ 30 , 31 , 32 , 33 ]. In this experiment, the polystyrene–divinyl benzene SPE column was used to recover α-conotoxin GI in the precipitating solvent.…”
Section: Discussionmentioning
confidence: 99%